Comparison of the effect of betanin on STAT3, STAT5, and KAP1 proteins in HepG2 and THLE-2 cells (Journal of Medical Science, 2023)
Background. Several studies suggest that the pleiotropic properties of betanin may interfere with different signaling pathways. Our previous studies on human hepatocytes showed that betanin activated the nuclear factor erythroid-2-related factor 2 (Nrf2) signaling pathway. To further understand the exact mechanism of action of betanin, we evaluated its effect on the levels of signal transducers and activators of transcription (STATs) and KRAB domain-associated protein 1 (KAP1) in hepatoma cells (HepG2) and normal human hepatocytes (THLE-2). Material and methods. HepG2 and THLE-2 cells were treated with 2 or 10 µM betanin for 72 h. The levels of STAT3, STAT5a, STAT5b, and KAP1 proteins in cytosolic and nuclear fractions were assessed by Western blot. Results. At a concentration of 10 μM, betanin significantly decreased the levels of STAT3, STAT5a, and STAT5b proteins in the nuclear fraction of HepG2 cells. On the other hand, no significant changes in the levels of STAT proteins were observed in THLE-2 cells. In HepG2 cells, betanin at both tested doses increased the level of KAP1. In contrast, in THLE-2 cells, betanin at a dose of 10 µM decreased the nuclear level of KAP1. Conclusions. Betanin modulated the levels of STAT3, STAT5, and KAP1 proteins, especially in hepatoma cells. Thus, it may be considered a potential therapeutic agent for the treatment of hepatoma.